The relation between eating behaviours and obsession among university students - Gezer, Ceren; Yalvaç, Mesut (Progress in Nutrition, 2018)
Aim: To investigate the relation between obsession and eating behaviours among university students including some factors that affected this relation. Methods: This cross-sectional study was conducted with 1754 university students. The study sample was selected using the stratified sampling method. Basic demographic data were collected. Eating attitudes were determined using the Eating Attitude Test (EAT)-40, and obsessive-compulsive behaviours were determined using the Maudsley Obsessive Compulsive Inventory (MOCI). Anthropometric measurements were also examined. Results: Females (16.2%) were observed to have higher risks of eating disorder than males (11.4%) (p<0.05). Eating disorder risk was also higher among students in the educational sciences (20.4%), health sciences (14.4%), applied sciences (11.8%) and social sciences (10.4%) (p<0.05). A positive relation was found between eating behaviour and obsession (r=0.337, p<0.001). Conclusion: The study found a relationship between eating behaviour and obsession. It also concluded that gender and education were the factors that affected eating behaviour and obsession.